Honesty Cultivation in School Children - สุรสกฺโก, พระมหาสุรศักดิ์; แก้วทองใหญ่, ยุทธวีร์ (Journal of Educational Review Faculty of Education in MCU, 2018)
It is regularly seen in our society that corruption and lack of honesty are increasing. Cultivating the youth with honesty is essential. This article is based on the teaching method through sub-articles called A Good Example of Honesty and Honesty in Daily Life. Each article was based on the Buddhist explanations with Jataka tales adapted from The Tipitaka. Story telling in the articles uses simple language suitable for children.